(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Ahara is as old as the history of humanity as the body is originated and subsequently maintained by food. Historically, by the fundamental methods as looking and accumulating and agriculture humans secured their food from nature. As agricultural technologies elevated, humans settled into agriculture existence with diets fashioned through the agriculture possibilities of their geographical environment. Geographic and cultural variations have caused creation of numerous cuisines and culinary arts, which includes a big selection of components, herbs, spices, techniques, and dishes. With engorgement of rapid transferring lifestyles, fashions of assimilation of various subculture and way of life the food become very venerable for life expectancy. In Ayurveda, proper style of partaking food or Ahara has been mentioned by different treatise in a holistic approach. In the present study the holistic measure regarding Ahara is stipulated in five common rights as the Right Quantity, Right Time, Right Quality, Right Method, and Right Place